Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1039/c9cc09132g
|View full text |Cite
|
Sign up to set email alerts
|

Carbon free silicon/polyaniline hybrid anodes with 3D conductive structures for superior lithium-ion batteries

Abstract: We design a carbon-free Si/polyaniline hybrid anode composed of porous Si dendrites and oxalic acid doped polyaniline coatings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Recently, selective dealloying is considered as a promising method for manufacturing micro-porous silicon. ( Luo et al, 2020 ; Zhou et al, 2020 ) This method employs cheap silicon-metal alloys (such as Si-Al alloys etc.) as raw materials, and porous silicon materials are obtained by removing metal elements in the alloys.…”
Section: Synthesis Of Porous Silicon-based Materialsmentioning
confidence: 99%
“…Recently, selective dealloying is considered as a promising method for manufacturing micro-porous silicon. ( Luo et al, 2020 ; Zhou et al, 2020 ) This method employs cheap silicon-metal alloys (such as Si-Al alloys etc.) as raw materials, and porous silicon materials are obtained by removing metal elements in the alloys.…”
Section: Synthesis Of Porous Silicon-based Materialsmentioning
confidence: 99%
“…Various approaches have been used to mitigate the drawbacks of Si-based materials, such as construction of flexible shells, integration of elastic binders, and doping of conductive atoms. [8][9][10][11][12][13] Among them, construction of flexible shells is one of the most efficient strategies to modify raw Si-based materials, owing to the capability of restraining the volume change and preventing electrolyte corrosion. Many studies have shown that the SiO x shell seems to be an essential choice due to its flexibility and electrochemical activity; 14 moreover, use of amorphous carbon coatings 15,16 is one of the most promising approaches to modify the shell of Si particles.…”
Section: Introductionmentioning
confidence: 99%
“…Various approaches have been used to mitigate the drawbacks of Si‐based materials, such as construction of flexible shells, integration of elastic binders, and doping of conductive atoms 8–13 . Among them, construction of flexible shells is one of the most efficient strategies to modify raw Si‐based materials, owing to the capability of restraining the volume change and preventing electrolyte corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, excellent anode material requires high specific capacity and cyclic stability. At present, ideal anode materials mainly include carbon, metal alloys and compounds 12‐17 . And it is the focus of current research to design anode active materials with novel structure and excellent performances.…”
Section: Introductionmentioning
confidence: 99%
“…At present, ideal anode materials mainly include carbon, metal alloys and compounds. [12][13][14][15][16][17] And it is the focus of current research to design anode active materials with novel structure and excellent performances. Hou et al 18 presented hollow TiO 2 sub-microspheres synthesized via a facile one-step, low temperature hydrothermal strategy.…”
Section: Introductionmentioning
confidence: 99%